ANALYSIS OF CLEAN WATER NEEDS IN RANOKOMEA VILLAGE, WEST POLEANG DISTRICT, BOMBANA REGENCY - Ayu Asriani; Nasarudin Nasarudin; Chairuddin Chairuddin (USN Kolaka, 2022)
The background of this research is the clean water in the village of Rakomea, which is inadequate because the amount of clean water discharge is not evenly distributed to all residential residents. This study aims to determine the clean water needs of the Ranokomea village community, West Poleang district, Bombana regency, in 2020 and the projected the year 2025. This research uses a quantitative descriptive research method with a sample of 81 family heads. The results showed that the needs for the net water of the people of Ranokomea village were 63,037 litres/person/day, and clean water needs in the year of 2025 projection namely 63.03 litres/person/day. Based on the feasibility standards of clean water needs issued by the UNESCO World Agency, namely 60 litres/person/day then, the needs of the people of Ranokomea village are not fulfilled because in 2020, people′s clean water needed 57.11 litres/person/day and in the year of 2025 projection namely 63.03 litres/person/day.